MIEJSCE PROSTYTUCJI W ATEŃSKIEJ SFERZE SACRUM W OKRESIE KLASYCZNYM - Nowak, Maria (Zeszyty Prawnicze, 2017)
Prostitution and SACRUM in Classical Athens Summary The article refers to the problem of prostitution at the field of laws regarding Athenian public worship. The participation in the cult of polis could be divided into some levels. The most advanced one is to be found in the societies supporting temple prostitution. Other forms of the access of prostitution into the holy sphere are, for instance, adoring a god/goddess protecting this group and simply giving it access into temples either as priests or simple worshippers. The last category is connected with public offerings as well. The paper is divided into four chapters, each concerning different aspect of the issue. The first one attempts to present Athenians’ attitude towards temple prostitution. The second one describes preserved particular laws excluding prostitutes from the sphere of sacrum. Then the case of Phano, basilinna accused of the profanation of Anthesteria is discussed. In the last chapter the question of exceptions from the above-said exclusion is deliberated. The paper is based mainly on the Attic oratory, especially on the speeches Against Neaira, Against Androtion preserved among Demothenes’ Speeches and on Aeschine’s Against Timarchos.